Дослідження кінетики зношування пар тертя: напилені покриття порошковим дротом системи Fe – Cr – Ni – Ti – Al — чавун СЧ30 - Богун, Лідія; Кушпір, Василь (КІНПАТРІ ЛТД, 2013)
The effective use of powder coatings deposited by wire system Fe - Cr - Ni - Ti - Al together with cast iron, under conditions of boundary lubrication was shown. Coatings posess superior triboengineering characteristics sn the range of 1.5 to 5 MPa. It was determsned that friction pair tested at 1 Mpa load operation requires prelapping operation during 1-2 hours. The optimal values for the equilibrium roughness for the studied friction pairs were found.
The kinetics investigation of wear of friction pairs: the coatings sprayed by Fe – Cr – Ni – Ti – Al— cast iron powder wire system